Importance of General Academic Vocabulary in Improving Writing Skills for Higher Secondary Students - M Pravena; Dr.V.K.Saravanan (Revista Electronica de Veterinaria, 2025)
Vocabulary plays a major role in English language teaching. It is the important tool to acquire four language skills of listening, speaking, reading and writing. General academic vocabulary is referred as high frequency words that are appears regularly in written text across the multiple subjects but not frequently used in conversational language. Language learners must be familiar with the academic words because of their academic purposes. Writing skills are the kind of skills used to communicate human thoughts and ideas in various written forms. The research points out some basic ways to improve writing skills of higher secondary students based on their writing practices in school: letter writing, paragraph writing, dialogue writing, essay writing, precise writing, developing hints, road map, describe the picture and note making, listing the vocabularies repeatedly used in writing skills in school level of writing. The results of the research find out general academic vocabulary as one of the important tool to improving higher secondary students writing skills in academic level.